Topoisomerase I has a strong binding preference for a conserved hexadecameric sequence in the promoter region of the rRNA gene from Tetrahymena pyriformis. - Andersen, A H (1985)
Topoisomerase I is in situ associated with DNaseI hypersensitive sites located in the promotor and terminator regions of the extrachromosomal rDNA in Tetrahymena thermophila at sites with sequences fitting the motif (sequence in text) Reconstitution experiments with purified topoisomerase I and cloned fragments of rDNA demonstrate that the enzyme exhibits the same binding and cleavage properties on naked DNA. These observations are striking as topoisomerase I previously has been found to exhibit low sequence specificity. The specific binding of the enzyme has an absolute requirement for divalent cations with a preference for Ca2+. The strong binding to the hexadecamer has been characterized by competition experiments, and it has been used to determine the molecular weight of the enzyme.